2013
DOI: 10.1098/rsif.2013.0312
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the aerodynamic performance by wing flexibility and elytra–hind wing interaction of a beetle during forward flight

Abstract: In this work, the aerodynamic performance of beetle wing in free-forward flight was explored by a three-dimensional computational fluid dynamics (CFDs) simulation with measured wing kinematics. It is shown from the CFD results that twist and camber variation, which represent the wing flexibility, are most important when determining the aerodynamic performance. Twisting wing significantly increased the mean lift and camber variation enhanced the mean thrust while the required power was lower than the case when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 39 publications
(44 reference statements)
8
72
0
Order By: Relevance
“…Taken together, the wings with the better camber performance presented the higher lift/power, which means less energy consumption, with neglecting the effects of AOA. It should be noted here that previous studies have reported an impressive improvement of efficiency for the flexible insect wings [6,10,31,44]. These results are consistent with the role of wing flexibility.…”
Section: Force Generationsupporting
confidence: 81%
See 1 more Smart Citation
“…Taken together, the wings with the better camber performance presented the higher lift/power, which means less energy consumption, with neglecting the effects of AOA. It should be noted here that previous studies have reported an impressive improvement of efficiency for the flexible insect wings [6,10,31,44]. These results are consistent with the role of wing flexibility.…”
Section: Force Generationsupporting
confidence: 81%
“…Wing flexibility is believed to be a key factor for the aerodynamic performance of insect flight [5]. Wing interaction characteristics and flexibility during the flapping motion are primary issues because they are believed to be the main reasons for the best aerodynamic performance of a flying insect [6]. A recent investigation of the effect of wing camber deformations on aerodynamic performance shows that wing deformations are important for enhancing efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…A numerical study (Young et al, 2009) with realistic wing shapes based on the high-speed photogrammetry suggested that the twist and camber can enhance the aerodynamic efficiency of the forward flight of locusts. Similar benefits of the wing deformation have been confirmed in the flight of butterflies or beetles in spite of the great differences in flight morphology (Le et al, 2013;Zheng et al, 2013).…”
Section: Introductionsupporting
confidence: 52%
“…Although flow visualizations on free and tethered dragonflies have shown some similar properties [12], the tethered flights can nevertheless convincingly reproduce the scenarios of free flight [13], in both kinematics [14] and force generation [15]. Hence, studies on the aerodynamics of insects in free flight are consistently pursued [16][17][18][19][20][21][22][23][24]. It has been pointed out that insects generate forces through a quite complex combination of aerodynamic mechanisms, including wake capture, active and inactive upstrokes, clap and fling, and LEV.…”
Section: Introductionmentioning
confidence: 99%